A chemiluminescence reagent free method for the determination of captopril in medicine and urine samples by using trivalent silver - Zhaofu Fu; Wanting Huang; Gongke Li; Yufei Hu (Elsevier, 2017)
A novel flow-injection chemiluminescence (FI-CL) method free of CL reagent was developed for the determination of captopril based on its enhancing effect on the CL derived from diperiodatoargentate(III)-sulfuric acid system. Compared with the conventional CL system, the CL system based on trivalent silver was characterized of good selectivity for the absence of CL reagent. The CL mechanism was discussed through CL spectra and UV-vis absorption spectra. The conditions of the FI-CL system were investigated and optimized. Under the optimal conditions, the relative CL intensity was linear with the captopril concentration in the range of 0.3-15.0 μg/mL. The detection limit for captopril was 0.05 μg/mL, and the relative standard deviation (n=11) was 2.0% for 5.0 μg/mL captopril. The proposed method was applied to the analysis of captopril in tablet and human urine with the recoveries of 83.1%-112.5%, and the relative standard deviations of 0.5%-4.4%. The results obtained by the proposed method agreed well with those obtained from HPLC method. The proposed method is fast, convenient, and cost-effective for the determination of captopril in medicine and biological samples.